Overexpression of yccL (gnsA) and ydfY (gnsB) Increases Levels of Unsaturated Fatty Acids and Suppresses both the Temperature-Sensitive fabA6 Mutation and Cold-Sensitive secG Null Mutation of Escherichia coli - Sugai, Rie (American Society for Microbiology, 2001)
A multicopy suppressor of the cold-sensitive secG null mutation was isolated. The suppressor contained sfa and yccL, the former of which has been reported to be a multicopy suppressor of the fabA6 mutation carried by a temperature-sensitive unsaturated fatty acid auxotroph. Subcloning of the suppressor gene revealed that yccL, renamed gnsA (secG null mutant suppressor), was responsible for the suppression of both the secG null mutation and the fabA6 mutation. In contrast, the sfa gene did not suppress the fabA6 mutation. The ydfY (gnsB) gene, encoding a protein which is highly similar to GnsA, also suppressed both the secG null mutation and the fabA6 mutation. Although both gnsA and gnsB are linked to cold shock genes, the levels of GnsA and GnsB did not exhibit a cold shock response. A gnsA-gnsB double null mutant grew normally under all conditions examined; thus, the in vivo functions of gnsA and gnsB remain unresolved. However, overexpression of gnsA and gnsB stimulated proOmpA translocation of the secG null mutant at low temperature and caused a significant increase in the unsaturated fatty acid content of phospholipids. Taken together, these results suggest that an increase in membrane fluidity due to the increase in unsaturated fatty acids compensates for the absence of the SecG function, especially at low temperature.